Factibilidad para la creación de una cafetería en el cantón Buena Fé, provincia de Los Ríos, año 2014 - Castro Vera, Jenny Aracely (2015)
The present research has as goal to demonstrate the feasibility for the creation of a Coffee Shop in Buena Fe City, Province of Los Rios. Therefore, the respective market study has been made, as well as the technical and financial studies. What is more, the most important results of these studies are detailed. In the market research study was determined that the creation of a Coffee Shop in Buena Fe city will have a market acceptance of 53%. It occurs because this percentage of peoples will be handy to go frequently while the 32% of them will do with much frequency. Also, it will be established the major competition companies in the market such as Delicias Coffee with a 31% of market share and D’Carlos with a 41%. About the technical study was established that the size for the shop should be of 24m2. The major level of services is for 40 customers per day of Mondays to Fridays and 50 customers per day of Saturdays to Sundays. The best location will be the street Franklin Torres y 7 de Agosto because it is one of the most popular and there are shops with spacious areas to the customers. In the financial study, it was determined that an initial investment of $ 18.299,49 USD for the implementation of the project which will be financed with a 78.77% through of a bank loan of Banco del Pichincha with an annual percentage rate of 15.20% for the purchase of equipment, machines and furniture while the 21.23% will funded by the Coffee Shop Manager. The analysis and financial evaluation found that the project is viable with a positive NPV of $ 22.946,81 and an IRR of 33.44% on the interest rate market, a benefit -cost ratio (B/ C) $1.11 USD which indicates that for every dollar invested a profit of $0.11 USD will be taken, and a capital recovery period in 4 years, 2 months 16 days.